On the Poisson's ratios of a woven fabric - Sun, Huiyu; Pan, Ning; Postle, Ron (Composite structures, 2005)
Although it is undeniable that the Poisson's effect on the behavior of a woven fabric is crucial, there have been relatively few papers devoted to this subject. In this study, a mechanical model for a woven fabric made of extensible yarns is developed to calculate the fabric Poisson's ratios. Theoretical results are compared with the available experimental data. A thorough examination on the influences of various mechanical properties of yarns and structural parameters of fabrics on the Poisson's ratios of a woven fabric is given. The prediction of Poisson's ratios in this paper will enable more rigorous studies on such important issues of fabric bending and draping behaviors.